Enhancing Student Achievement in Senior High School through Curriculum Management in Indonesia - Zulkifli Zulkifli; Pham Vu Phi Ho; Muh Ibnu Sholeh; Sahri Sahri (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study is to examine student accomplishment, the management of the high school curriculum, and the creation, application, and effects of the curriculum on student achievement. Qualitative research methodologies were employed in this study. Observations and in-depth interviews with educators, school administrators, and other staff members provided the data. A qualitative transcribing approach was employed to examine the data, followed by coding, grouping the key findings of the research, and conclusion. The study's findings indicate that students are on the right track to achieve extraordinary achievements with continuous measurement and evaluation; an interactive learning approach can enhance students' learning experiences, and an educational environment that supports student achievement has been established. Combining these elements has allowed this school to effectively educate its pupils for various competitive and competitive difficulties, making them resilient in the long run. This study emphasizes how important it is for secondary schools to manage their curricula effectively to increase student accomplishment by providing students with relevant, interest-based material. To further improve educational outcomes, interactive learning strategies, more resources, and continuous assessment are helpful.